Preliminary Culture Studies of Microalgae Isolated from the Freshwater Tributaries of Carigara bay, Leyte, Philippines - Soriano, Hernando Alice Geraldine; Fernando, Baldia, Susana (Asian Journal of Biological and Life Sciences, 2020)
Phytoplankton is the base or the bottom of the aquatic food chain and serve as primary producers. Meanwhile, Carigara bay is one of the most successful fishing lands in the Philippines but there are still scarcity of literatures regarding the bay, connected freshwater resources and biological components of the aquatic environment. Therefore, this study was explored. Sampling was conducted on the 5 coastal towns surrounding the bay. Water samples from the stream, rivers and falls were collected using a 2.5-3L Plexi glass sampler, transferred in 3 1L cap bottle and brought in the laboratory for isolation of phytoplankton. Isolation was done using Binangonan Research Station Pantastico or BRSP medium. Preliminary culture studies were conducted to selected phytoplankton namely Genus Anabaena, Oscillatoria, Asterococcus and Chlorococcum. The 4 phytoplankton were preliminary optimized in terms of light intensities, pH and temperature. Cell density in every 2 days was gathered through haemacytometer method and specific growth rate was computed. Mean and standard deviations were used to summarize the data in optimized results for the light intensities, temperature and pH desired by the isolated phytoplankton and data were further subjected to Analysis of Variance (ANOVA). The 4 phytoplankton grow best at 3000 lux, pH 7.27 and 25°C according to the optimization procedure conducted. It can be also noted that the optimization tests is important to sustain the mass production of phytoplankton.
Keywords: Initial; isolation; Microalgae; Optimization; Tributaries